Cover Crop System to Control Charcoal Rot in Soybeans - Gretchen Sassenrath; C. R. Little; C. J. Hsiao; D. E. Shoup; X. Lin (Kansas Agricultural Experiment Station Research Reports, 2017)
This research compares methods of controlling charcoal rot in soybean cultivars from three maturity groups commonly grown in southeast Kansas. The results indicate that a mustard plant that produces high levels of glucosinolates can be used as a cover crop to reduce the charcoal rot disease in soybeans.
Keywords: soybean; charcoal rot; cover crops